(untitled) (Journal of the College of Basic Education, 2023)
The present study aims at examining a frequently-occurring element of the unique style of the Quran, i.e. puns. Adopting pun translation strategies outlined in Delabastita (2004) as a basis of measurement, the Quran and its two English renderings are hence analyzed to explore what strategies are applied by the translators on the one hand, and to discover the extent of (un)translatability of puns of the Qur’an, on the other hand. The results of the study revealed how feasible the strategies proposed by Delabastita (2004) in his theoretical framework are in terms of the (un)translatability of puns in the case of the Quran. The findings of the study will hopefully pave the way for further investigations on the translatability of different issues in Muslims’ Holy Scripture. Also, the findings can be reconfirmed in future studies on other sacred books towards a possible generalization.